2007
DOI: 10.1080/01485010600908330
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Survival: Relationship to Age-Related Sperm DNA Integrity in Infertile Men

Abstract: The purpose of our study was to evaluate the effect of age and sperm DNA integrity on sperm survival. Semen samples from fifty six unselected patients undergoing infertility evaluation were assessed in terms of standard semen parameters, DNA integrity, and sperm survival after 6-24 h of incubation. Prolonged incubation of density gradient selected sperm adversely effects sperm survival in older patients and patients with extensive sperm DNA damage. Immediate preparation of such samples prior to use for assiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…The mature sperm fraction prepared by density-gradient centrifugation has improved longevity and sperm DNA integrity (53), although a recent report recommended immediate semen preparation before use for ART to overcome the negative effect of extended (6-24 hour) incubation (54). The aim of this study was to evaluate the association of sperm chromatin integrity and maturity with sperm apoptotic stages and the apoptotic subpopulation in unprocessed as well as mature and immature sperm fractions processed by density-gradient separation.…”
Section: Discussionmentioning
confidence: 99%
“…The mature sperm fraction prepared by density-gradient centrifugation has improved longevity and sperm DNA integrity (53), although a recent report recommended immediate semen preparation before use for ART to overcome the negative effect of extended (6-24 hour) incubation (54). The aim of this study was to evaluate the association of sperm chromatin integrity and maturity with sperm apoptotic stages and the apoptotic subpopulation in unprocessed as well as mature and immature sperm fractions processed by density-gradient separation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated an increase in sperm DNA damage with age in healthy [8,31,32] and infertile men [33][34][35]. DNA fragmentation has been proposed as one of the reasons for the negative paternal effects on reproductive outcome, because a high percentage of DNA fragmentation has been correlated with low pregnancy rate [36].…”
Section: Discussionmentioning
confidence: 99%
“…However, no association could be determined with an increase in aneuploidy/diploidy or specific FGFR2 mutations. An increase in DNA fragmentation (demonstrated by TUNEL assay and SCSA) and poor chromatin packaging (by CMA 3 staining) has been linked to OAT patients with increased age (Moskovtsev et al. , 2006, 2007; Plastira et al.…”
Section: Introductionmentioning
confidence: 99%